Strategies for embolization of direct arteriovenous shunts in brain arteriovenous malformations - Clarençon, Frédéric; Shotar, Eimad; Lenck, Stéphanie; Aubertin, Mathilde; Premat, Kevin; Boch, Anne-Laure; Sourour, Nader-Antoine (Journal of neurointerventional surgery, 2021)
Intranidal direct arteriovenous (AV) shunts are rarely observed in brain arteriovenous malformations (bAVMs).1 The endovascular treatment of such direct AV shunts may be challenging. Indeed, there is a significant risk of venous migration of the embolic agent used to occlude the AV shunt, leading to a subsequent risk of nidus bleeding due to impairment (slowdown or even occlusion) of the bAVM’s venous drainage.2Various endovascular techniques have been developed to avoid the risk of such inopportune impairment of the venous drainage during attempts to occlude a direct intranidal AV shunt.3–5 We present in this Technical Video (video 1) different endovascular strategies to occlude such direct AV shunts using dual-lumen balloons with various liquid embolic agents, or using occlusion plugs.Video 1media110.1136/neurintsurg-2021-017317.video016236501366001neurintsurg2021017317media1